CXCR4 Antagonism Reduces Cardiac Fibrosis and Improves Cardiac Performance in Dilated Cardiomyopathy - Chu, Po-Yin; Joshi, Mandar S.; Horlock, Duncan; Kiriazis, Helen; Kaye, David M. (Frontiers in Pharmacology, 2019)
Background Myocardial fibrosis is a key pathologic finding in the failing heart and is implicated as a cause of increased ventricular stiffness and susceptibility to ventricular arrhythmia. Neurohormonal mediators such as aldosterone and angiotensin II are known to cause fibrosis in experimental models, however clinical evidence for the reversal of fibrosis with relevant antagonists is limited. Recent studies suggest that inflammatory mediators may contribute to fibrosis. In dilated cardiomyopathy the mechanism for myocardial fibrosis is unclear and its implications on systolic function are not known. Methods and Results We studied the effect of a highly selective antagonist of SDF-1/CXCR4 signaling, AMD3100, on the development of cardiac fibrosis and cardiac function in mice with dilated cardiomyopathy due to cardiac-specific transgenic overexpression of the stress-kinase, Mst1. AMD3100 significantly attenuated the progression of myocardial fibrosis and this was accompanied by significant improvements in diastolic and systolic performance as evaluated in isolated Langendorff perfused hearts. AMD3100 reduced BNP mRNA expression but did not alter the expression of Ca2+ handling genes. CXCR4 antagonism also reduced the abundance of splenic CD4+ T cells. Conclusions This study demonstrates that CXCR4 pathway contributes to pathogenesis of cardiac fibrosis in dilated cardiomyopathy, and it represents a new potential therapeutic target in heart failure. The data also demonstrate that anti-fibrotic strategies can improve systolic performance.